Cryopreserved human adipose-derived stromal vascular fraction maintains fracture healing potential via angiogenesis and osteogenesis in an immunodeficient rat model - Kamenaga, Tomoyuki (Stem Cell Res Ther, 2021)
BACKGROUND: Novel therapeutic strategies for the healing of nonunion, which has serious effects on the quality of life of patients, are needed. We evaluated the therapeutic effect of local transplantation of human stromal vascular fraction (SVF) cells on fracture healing in a rat non-healing fracture model and compared the effects between freshly isolated (F) and cryopreserved (C)-SVFs. METHODS: Non-healing fracture model was induced in the femur of female immunodeficient rats (F344/N Jcl rnu/rnu) with cauterizing periosteum. Immediately after the creation of non-healing fracture, rats received local transplantation of F and C-SVFs suspended in phosphate-buffered saline (PBS) or the same volume of PBS without cells using the same scaffold as a control group. During 8 weeks post-surgery, radiologic, histological, immunohistochemical, and biomechanical analyses were performed to evaluate fracture healing. The comparison of radiological results was performed with a chi-square test, and the multiple comparisons of immunohistochemical, histological, and biomechanical results among groups were made using a one-way analysis of variance. A probability value of 0.05 was considered to denote statistical significance. RESULTS: At week 8, in 60% of animals receiving F-SVF cells and in 50% of animals receiving C-SVF cells, the fracture radiologically healed with bone union whereas nonunion was observed in the control group. The healing potential was also confirmed by histological and biomechanical assessments. One of the mechanisms underlying healing involving intrinsic angiogenesis/osteogenesis was enhanced in F- and C-SVF groups compared with that in the control group. Human cell-derived vasculogenesis/osteogenesis, which was also confirmed in an in vitro differentiation assay, was also enhanced in the F- and C-SVF groups compared with that in the control groups and could be another mechanism for healing. CONCLUSIONS: SVF cells can enhance bone healing and cryopreserved cells have almost equal potential as fresh cells. SVF cells can be used for improving nonunion bone fracture healing as an alternative to other mesenchymal stem cells and the effect of SVF cells can be maintained under cryopreservation.